Green human resource management and organizational performance: A systematic literature review - Esmeralda, Angel II P. (Social Sciences Insights Journal, 2025)
This systematic literature review examines the relationship between green human resource management (GHRM) practices and organizational performance outcomes. The review synthesizes empirical evidence from 82 studies published between 2019 and 2024, addressing multiple dimensions of performance including environmental, financial, social, and sustainable performance. Following PRISMA 2020 guidelines, a systematic search was conducted across Scopus, Web of Science, and Google Scholar databases. Studies were analyzed using the Ability-Motivation-Opportunity (AMO) theoretical framework to categorize GHRM practices and their performance implications. The evidence strongly supports positive relationships between GHRM practices and organizational performance. Environmental performance shows the most consistent positive effects, followed by sustainable performance and green innovation. The GHRM-financial performance relationship is predominantly indirect, mediated by environmental performance and employee green behavior. Green training and development emerges as the most frequently examined and impactful practice. Employee green behavior serves as a critical mediating mechanism across all performance dimensions. This review provides an integrated framework connecting GHRM practices to multi-dimensional organizational performance through the AMO lens. It identifies critical mediating mechanisms and moderating factors, offering actionable insights for practitioners seeking to leverage human resources for environmental sustainability while maintaining competitive performance.